PERAN PERPUSTAKAAN UMUM DALAM MENINGKATKAN MINAT BACA DI DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN JEMBRANA - Jihadarsana Maheswara, I Ketut Cesario; Haryanti, Ni Putu Premierita; Haryanti, Ni Putu Premierita; Suhartika, I Putu (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2022)
This research tries to explore the role of public library in increasing reading interest in the Jembrana Regency Archives and Library Service in 2021. Quantitative Descriptive Research Method is used in this study. It is also used questionnaire and literature study in collecting the data. This study uses sampling method and 296 people are used as sample. The result of this study indicates that the people visitthe Public Library is to gain information and knowledge because of its sufficient and appropriate collections. The source of information found in the library helps the readers to increase their motivation in reading. In conclusion, the public library has significant role in increasing reading interest.